CHRONIC PROSTATITIS AND ITS DIAGNOSIS: CLINICAL AND LABORATORY EVALUATION (International journal of medical sciences, 2025)
Chronic prostatitis (CP) is a prevalent urological condition characterized by persistent pelvic pain, lower urinary tract symptoms, and sexual dysfunction. This retrospective study evaluated 80 male patients with CP admitted to the Urology Department of [Hospital/Institute Name] between January 2021 and June 2025. Clinical assessment included detailed patient history and digital rectal examination (DRE). Laboratory investigations involved urinalysis, urine culture, expressed prostatic secretions (EPS) analysis, and prostate-specific antigen (PSA) measurement. Imaging studies included transrectal ultrasonography (TRUS) and, in selected cases, magnetic resonance imaging (MRI). The majority of patients exhibited pelvic pain for more than six months (65%), urinary frequency (70%), dysuria (55%), and sexual dysfunction (40%). EPS analysis revealed elevated leukocyte counts in 55% of patients, and positive bacterial cultures in 30%, with Escherichia coli being the most common pathogen. TRUS showed increased prostate volume and heterogeneous echotexture in 62% of patients, while MRI confirmed inflammatory changes without neoplastic lesions. The results indicate that an integrated approach combining clinical, laboratory, and imaging evaluation is essential for accurate diagnosis and management of CP.